Dermoscopic evaluation of superficial spreading melanoma, - Fernanda Marques Trindade; Maria Luiza Pires de Freitas; Flávia Vasques Bittencourt (Sociedade Brasileira de Dermatologia, 2021)
Abstract Background: Dermoscopy increases the sensitivity of the diagnosis of melanoma, leading to its early identification and increasing the chances of cure. Objective: To describe the clinical and dermoscopic characteristics of superficial spreading melanomas, and to detect the differences between in situ and invasive 1-mm thick melanomas. Methods: This was a cross-sectional study in which dermoscopic images of 58 melanomas, grouped according to their thickness, were evaluated. Results: 24 in situ melanomas were evaluated, 28 invasive melanomas with Breslow ≤ 1 mm (0.50 ± 0.22 mm) and six with Breslow > 1 mm (2.35 ± 2.02 mm). In situ melanomas were smaller than invasive melanomas. The most commonly found dermoscopic criteria were asymmetry (84.5%), three or more colors (81.0%), and atypical network (79.3%). A non-specific pattern was more common in in situ melanomas (p = 0.028) and atypical network in invasive melanomas with Breslow 1 mm presented inverted network (p = 0.018). Study limitations: The sample was selected by convenience, since it was necessary to have a preoperative photo of the tumor, which may have led to the loss of clinically less significant lesions, as well as those highly suggestive of melanoma. Conclusions: Melanomas in early stages showed a more frequent nonspecific pattern and atypical network, while invasive melanomas showed a multicomponent pattern, three or more colors, and an inverted network.